Development of biocementation methods for sandy soil - Tan, Eugene Guan Long. (2011)
In the recent times, chemical grouting is being employed to improve mechanical strength of the soil formation and to reduce the soil hydraulic conductivity. However, there are disadvantages in adopting chemical grouting as means of soil improvement. Chemical grouting brings about environmental pollution to the surroundings as well as incurring high costs associated with machinery, equipments and chemicals. Hence for an alternative to chemical grouting, biological soil treatment in-situ would be a potential solution to overcome the shortcomings from chemical groutings.